Results from 37 years of mortality experience among US underground coal miners. (19th October 2011) - Graber, Judith; Attfield, Michael; Stayner, Leslie
Abstract : Objectives: Evaluate the mortality experience of 8889 underground coal miners over 36–38 years. Methods: Underlying cause of death was assessed in miners enrolled between 1969 and 1971 from 31 U.S. mines and evaluated with life-table analysis. Poisson models were fitted to evaluate cumulative exposure to coal-mine dust (CMD; mg-year/m3) controlling for smoking, age, coal-rank region, and calendar year. Results: Elevated mortality among 5925 deaths was observed for non-malignant respiratory disease (SMR 1.76, 95% CI 1.65 to 1.87), including pneumoconiosis (SMR 77.68, 95% CI 70.24 to 85.69), but not for COPD (SMR 1.08, 95% CI 0.97 to 1.21). Protective effects were seen for mortality from all causes, all cancer and heart and circulatory diseases. Excess mortality was seen for multiple myeloma among non-white (SMR 2.84, n=6) but not white miners (SMR 0.93, n=22), and for conductive-heart disorders (SMR 1.64, 95% CI 1.39 to 1.92). A linear exposure-response association with CMD was observed for pneumoconiosis (RR 1.005, 95% CI 1.003 to 1.006, p<0.0001); COPD among former/non-smokers (RR 1.0045, 95% CI 1.0016 to 1.0075; p=0.0026), but not current smokers (RR 1.0005, 95% CI 0.9982 to 1.0027; p=0.6915) and for multiple myeloma among non-white miners (RR 1.0221, 95% CI 1.0064 to 1.0380; p= 0.0058) but not white miners (RR 1.0014, 95% CI 0.9939 to 1.0090; p=0.7133). No excess mortality or trend in E-R was observed for lung or stomach cancer. Conclusions: Our findings expand upon previous results showing that CMD exposure leads to increased mortality form respiratory disease, even in the absence of smoking. A healthy worker effect was seen for some but not all cancer and heart-disease related mortality; an unexpected excess of multiple myeloma among non-white miners was observed.